2005
DOI: 10.1038/nm1337
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor determines sensitivity to inhibitors of mTOR in kidney cancer

Abstract: Inhibitors of the kinase mammalian target of rapamycin (mTOR) have shown sporadic activity in cancer trials, leading to confusion about the appropriate clinical setting for their use. Here we show that loss of the Von Hippel-Lindau tumor suppressor gene (VHL) sensitizes kidney cancer cells to the mTOR inhibitor CCI-779 in vitro and in mouse models. Growth arrest caused by CCI-779 correlates with a block in translation of mRNA encoding hypoxia-inducible factor (HIF1A), and is rescued by expression of a VHL-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
398
2
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 573 publications
(415 citation statements)
references
References 20 publications
10
398
2
5
Order By: Relevance
“…Indeed, we determined by quantitative RT-PCR that PTND111-136 significantly down-regulated the expression of genes involved in hypoxia and the angiogenesis pathway such as VEGF-A as suggested previously (38). Moreover, further experiments are warranted to explain these results and more particularly to explore the role of PTND111-136 in phosphoinositide 3-kinase/Akt/mammalian target of rapamycin signaling, because the expression of HIF-1a and VEGF-A was recently shown to be dependent on the mammalian target of rapamycin pathway (39,40).…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, we determined by quantitative RT-PCR that PTND111-136 significantly down-regulated the expression of genes involved in hypoxia and the angiogenesis pathway such as VEGF-A as suggested previously (38). Moreover, further experiments are warranted to explain these results and more particularly to explore the role of PTND111-136 in phosphoinositide 3-kinase/Akt/mammalian target of rapamycin signaling, because the expression of HIF-1a and VEGF-A was recently shown to be dependent on the mammalian target of rapamycin pathway (39,40).…”
Section: Discussionmentioning
confidence: 55%
“…Several studies have suggested that the mTOR inhibitor rapamycin can decrease HIF-1a expression (18,21,(38)(39)(40). However, we found that treatment of U87MG cells with 10 nmol/L of the drug had no effect on HIF-1a expression in response to either CoCl 2 or hypoxia (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Therefore, cellular changes, such as loss of intercellular junctions and epithelial de-differentiation involving HIFdependent as well as HIF-independent molecular pathways 48,[106][107][108] in addition to HIF-dependent and -independent alterations in p53 or NF-kB activity, 34,35,49,51 HGF signaling, 45,50,109 and modifications in ECM turnover and re-modeling [42][43][44][45][46][47] create the molecular environment for the development CC-RCC, which most likely requires additional genetic events. The importance of HIF activation in CC-RCC pathogenesis and growth is furthermore underscored by experimental and clinical studies, which demonstrated that inhibition of HIF-a translation by pharmacological targeting of mTOR correlated with reduced tumor growth, 110 and that increased expression of certain HIF target genes, such as CXCR4, as well as E-cadherin suppression was associated with disease progression. 111,112 With regard to the contribution of individual HIF-a homologs to renal tumor development, it is of interest that a substantial number of VHL-defective CC-RCC cell lines do not express HIF-1a, but express HIF-2a.…”
Section: Pvhl and Renal Cell Cancermentioning
confidence: 99%